2020
DOI: 10.1186/s12934-020-01325-0
|View full text |Cite
|
Sign up to set email alerts
|

Robust microorganisms for biofuel and chemical production from municipal solid waste

Abstract: Background: Worldwide 3.4 billion tonnes of municipal solid waste (MSW) will be produced annually by 2050, however, current approaches to MSW management predominantly involve unsustainable practices like landfilling and incineration. The organic fraction of MSW (OMSW) typically comprises ~ 50% lignocellulose-rich material but is underexplored as a biomanufacturing feedstock due to its highly inconsistent and heterogeneous composition. This study sought to overcome the limitations associated with studying MSW-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 96 publications
(123 reference statements)
1
15
0
Order By: Relevance
“…Dornau et al analyzed the potential of eight biotechnologically useful microorganisms ( Clostridium saccharoperbutylacetonicum , Escherichia coli , Geobacillus thermoglucosidasius , Pseudomonas putida , Rhodococcus opacus , Saccharomyces cerevisiae , Schizosaccharomyces pombe , and Zymomonas mobilis ) to grow and produce diverse bioproducts from OMSW. Enzymatic hydrolysate of OMSW fiber contained high concentrations of glucose (5.5%, w / v ) and xylose (1.8%, w / v ) but was deficient in nitrogen and phosphate [ 91 ]. Interestingly, three species ( Z. mobilis , S. cerevisiae, and R. opacus ) became more efficient during OMSW fiber hydrolysate fermentation.…”
Section: Conversion Of Industrial Wastes Into Microbial Oils By Rhodococcimentioning
confidence: 99%
See 2 more Smart Citations
“…Dornau et al analyzed the potential of eight biotechnologically useful microorganisms ( Clostridium saccharoperbutylacetonicum , Escherichia coli , Geobacillus thermoglucosidasius , Pseudomonas putida , Rhodococcus opacus , Saccharomyces cerevisiae , Schizosaccharomyces pombe , and Zymomonas mobilis ) to grow and produce diverse bioproducts from OMSW. Enzymatic hydrolysate of OMSW fiber contained high concentrations of glucose (5.5%, w / v ) and xylose (1.8%, w / v ) but was deficient in nitrogen and phosphate [ 91 ]. Interestingly, three species ( Z. mobilis , S. cerevisiae, and R. opacus ) became more efficient during OMSW fiber hydrolysate fermentation.…”
Section: Conversion Of Industrial Wastes Into Microbial Oils By Rhodococcimentioning
confidence: 99%
“…Interestingly, three species ( Z. mobilis , S. cerevisiae, and R. opacus ) became more efficient during OMSW fiber hydrolysate fermentation. R. opacus MITXM-61 produced TAG to 72% of the maximum theoretical fermentation yield and could theoretically produce 91 kg of TAG per tonne of OMSW [ 91 ]. R. opacus MITXM-61 is an engineered strain [ 95 ] with the ability to simultaneously utilize D-glucose and D-xylose in lignocellulosic hydrolysates.…”
Section: Conversion Of Industrial Wastes Into Microbial Oils By Rhodococcimentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the moisture content of the as-made biofiber was around 70% on total wet weight. Previous analyses had shown that the biofiber from the standardized MSW comprised of approximately 58% w/w lignocellulose, of which 65.5% was cellulose (38% of total fibre), 27.6% was lignin (16% of total fibre) and 6.9% was hemicellulose (4% of total fibre) [18]. The high cellulose content suggested that the biofiber would be a practicable fermentation feedstock.…”
Section: Biofiber Feedstocksmentioning
confidence: 99%
“…Much research states that microorganisms are still the biggest group of undescribed biodiversity and that they are a bewildering source of exploitable diversity [1]. Municipal solid waste (MSW) refers to waste coming out of homes and institutions, and over 2 billion tonnes are produced worldwide on an annual basis, with a 2050 projection of 3.4 billion tonnes [2]. The collection, management, and disposal of MSW are a huge environmental issue causing huge environmental problems such as air, water, soil, and esthetic pollution [3].…”
Section: Introductionmentioning
confidence: 99%